Estudo do perfil metabolômico de folhas de cajazeira, umbuzeiro e abacaxizeiro e sua correlação com potencial atividade anticâncer por meio de análise multivariada - Guedes, Jhonyson Arruda Carvalho (2019)
The use of co-products from the fruit agroindustry as a source of bioactive molecules presents economic advantages since these compounds are available at a low cost and may present an alternative of adding value to this highly available raw material. Therefore, the present study had as objective to evaluate the metabolomic profile of the leaves of cajazeira, umbuzeiro and seven varieties of pineapple, correlating the chemical profiles to cytotoxicity tests. The hexane extracts of cajazeira, umbuzeiro and seven varieties of pineapple and the hydroalcoholic extracts of leaves of cajazeira and umbuzeiro were analyzed. The metabolic profiles of the hexane extracts were established via GC-MS, in the cassava and umbuzeiro leaves 23 different metabolites were identified in the cultivars of pineapple were identified 27. The hydroalcoholic extracts of the leaves of cajazeira and umbuzeiro were analyzed by UPLC-QTOF-MSE allowing the identification of 43 metabolites. Through the multivariate analysis (PCA, HCA, PLS-DA and OPLS-DA), it was possible to correlate the metabolomic profiles with the respective cytotoxic activities, through the identification of the respective biomarkers. The hexanic extracts of the umbuzeiro showed high activity against all the tumoral lines including the healthy cells, being, therefore, to be infeasible, to present high cytotoxicity. However, the extract of cajazeira presented inhibitory activity relevant to the prostate cancer strain (75.28%); in addition, a good selectivity index was verified in relation to the healthy cell line (44.63%). In relation to the hexanic extracts of the seven varieties of pineapple, promising cytotoxic activity against the six tumor lines tested (colon, leukemia, prostate, astrocytoma, breast and uterine cervix) was generally verified, in this case, the biomarkers that were tentatively associated with the cytotoxic activity. In the hydroalcoholic extracts, the cytotoxicity assays demonstrate that the leaves of cassava have better cytotoxic activity when compared to the umbuzeiro leaves. The best results were obtained against leukemia and melanoma tumor cell lines. The validation of the biomarkers found by chemometric methods was performed through comparisons, using theoretical calculations involving molecular orbitals, which represented an innovation in the field of metabolomic studies.